Early antiretroviral therapy initiation in west Africa has no adverse social consequences: a 24-month prospective study. (19th June 2016) - Jean, Kévin; Niangoran, Serge; Danel, Christine; Moh, Raoul; Kouamé, Gérard Menan; Badjé, Anani; Gabillard, Delphine; Eholié, Serge; Dray-Spira, Rosemary; Lert, France; Anglaret, Xavier; Desgrées-Du-LoÛ, Annabel
Abstract : Based on social indicators collected within the TEMPRANO-ANRS12136 trial, we assessed the social consequences of early antiretroviral therapy (ART) initiation in west Africa. We did not observe any significant differences in the levels or the time trends of various social indicators, including union status, HIV disclosure and HIV-related discrimination, between early and deferred ART initiation. Early ART does not carry detectable adverse social consequences that could impair its clinical and preventive benefits. Abstract : Supplemental Digital Content is available in the text